Spirulina platensis effect on oxidative stress of rat’s offspring brain exposed to cigarette smoke during pregnancy and lactation - Kenny Cantika Abadi; Febriana Catur Iswanti; Sri Widia A Jusman; Ani Retno Prijanti; Fadilah Fadilah (Indonesian Society for Biochemistry and Molecular Biology, 2022)
Background: Maternal exposure to cigarette smoke during pregnancy and lactation might harmful for the fetus. The smoke contains many free radicals that could be eliminated by antioxidant. This study aimed to investigate the effect of Spirulina platensis ethanol extract as antioxidant against cigarette smoke exposure during pregnancy until lactation by assessing oxidative stress markers in neonatal brain tissues. Methods: The experimental study used 26 offspring divided into four groups: (C) = offspring of maternal control group; (Cg) = offspring of maternal exposed to cigarette smoke; (CgSp) = offspring of maternal given spirulina and exposed to cigarette smoke; and (Sp) = offspring of maternal given spirulina only group, during gestation and 9 days lactation (30 days). Each group consisted of 6 offspring obtained from 2 adult females mated with male Sprague-Dawley rats. The exposure of cigarette smoke was 4 burn cigarettes/day for 30 days. The dose of extract was 200 mg/kg BW. The offspring were sacrificed, and the brain tissues were taken for MDA, MnSOD activity, as well as catalase activity, carbonyl, and GSH. Results: There was no significant differences in MDA level between groups. The carbonyl, SOD, and catalase activity did not differ between the control and smoked group. Conclusion: Exposure of four burned cigarettes smoke per day during pregnancy, and 9 days of lactation did not trigger oxidative stress. However, the effect of Spirulina platensis administration on rat offspring brain could not be analyzed.